UPLC-PDA factorial design assisted method for simultaneous determination of oseltamivir, dexamethasone, and remdesivir in human plasma - Hanan I. EL-Shorbagy; Mona A. Mohamed; Alaa El-Gindy; Ghada M. Hadad; Fathalla Belal (Scientific Reports, 2024)
Abstract A green and simple UPLC method was developed and optimized, adopting a factorial design for simultaneous determination of oseltamivir phosphate and remdesivir with dexamethasone as a co-administered drug in human plasma and using daclatasvir dihydrochloride as an internal standard within 5 min. The separation was established on UPLC column BEH C18 1.7 μm (2.1 $$× $$ × 100.0 mm) connected to UPLC pre-column BEH 1.7 μm (2.1 $$× $$ × 5.0 mm) at 50 °C with an injection volume of 10 μL. The photodiode array detector (PDA) was set at three wavelengths of 220, 315, and 245 nm for oseltamivir phosphate, the internal standard, and both dexamethasone and remdesivir, respectively. The mobile phase consisted of methanol and ammonium acetate solution (40 mM) adjusted to pH 4 in a ratio of 61.5:38.5 (v/v) with a flow rate of 0.25 mL min−1. The calibration curves were linear over 500.0–5000.0 ng mL−1 for oseltamivir phosphate, over 10.0–500.0 ng mL−1 and 500.0–5000.0 ng mL−1 for dexamethasone, and over 20.0–500 ng mL−1 and 500.0–5000.0 ng mL−1 for remdesivir. The Gibbs free energy and Van't Hoff plots were used to investigate the effect of column oven temperatures on retention times. Fluoride-EDTA anticoagulant showed inhibition activity on the esterase enzyme in plasma. The proposed method was validated according to the M10 ICH, FDA, and EMA’s bioanalytical guidelines. According to Eco-score, GAPI, and AGREE criteria, the proposed method was considered acceptable green.